PENGARUH INFLASI, NILAI KURS RUPIAH, DAN TINGKAT SUKU BUNGA TERHADAP HARGA SAHAM DI BURSA EFEK (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia). - Sri Mulyati, 09.05.51.0021; Subagyo, Herry (Students Journal of Economic and Management, 2013)
This study aims to examine and analyze the effect of inflation, exchange rate, and interest rates on stock prices on the stock exchange Indonesia. The data in this study, using secondary data that is obtained from the central bank BPS and Indonesia. The analysis in this study using multiple linear regression analysis with the SPSS program. The test results show that inflation, exchange rate, and interest rates has a positive effect onstock prices in Indonesia. Results for the multiple linear regression showed that inflation of 0,268, the value of the exchange rate of 0,142, 0.144 and interest ratesKey words : Inflation, Exchange Rate Value, Interest Rate and Stock Price.